Effect of 3-hydrazinylquinoxaline-2-thiol hydrogel on skin wound healing process in diabetic rats - Jehan Barakat Alamre; Huda Alkreathy; Ahmed S. Ali; Abdelbagi Alfadil; Sahar S. Alghamdi (Scientific Reports)
Abstract Impaired wound healing in diabetic individuals creates huge social and financial burdens for both diabetic patients and the health system. Unfortunately, the current treatment has not resulted in consistently lower amputation rates. Quinoxalines are heterocyclic compounds with multiple important pharmacological properties. Their effect on wound healing have not been closely studied. In the current work, the wound healing effect of 3-hydrazinylquinoxaline-2-thiol hydrogel is tested topically in a full-thickness excision wound in streptozotocin-induced type 1 diabetic rats. We examined the wound closure rate, expression of inflammatory factors, growth factors in addition to the histological analysis. The results revealed a significant acceleration in wound closure in the treated group compared with the control experimental animals. Histological data demonstrated enhanced re-epithelialization and collagen disposition. The healing effect was additionally evaluated by the inhibition of the inflammatory response of interleukin (IL)—1β interleukin (IL)—6, tumor necrosis factor (TNF-α) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) with a marked improvement of the transforming growth factor beta (TGFβ-1), antioxidant markers and collagen-1. In silico study indicated a favorable drug-like properties and toxicity profile. The present work showed that 3-hydrazinylquinoxaline-2-thiol holds great potential for the treatment of diabetic wounds.